2021
DOI: 10.1002/aoc.6559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of defected UIO‐66 with boosting the catalytic performance via rapid crystallization

Abstract: Due to environmental and health concerns, it is very important to develop high activity oxidative desulfurization (ODS) catalyst for petroleum purification. Recently, defect engineering of metal organic frameworks (MOFs) to generate a large number of unsaturated catalytic active sites is a very promising approach. Defective MOF has good research value as ODS catalyst. Here, UIO‐66 with lots of defects can be prepared by rapid crystallization using concentrated hydrochloric acid as a modulator. The prepared UIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additionally, we narrowed the focus to UiO-66 without functionalization or any kind of postsynthetic modification, as well as excluding UiO-66 analogues such as UiO-67. The final data set (included in the Supporting Information) is intended to be a representative, but not a comprehensive summary of the current literature and comprises of 293 samples across 37 papers, ,,, ,,, representing a publication period from 2011 to 2022. The distribution of the data set across input and output variables is also presented in the Supporting Information.…”
Section: Data Collection and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we narrowed the focus to UiO-66 without functionalization or any kind of postsynthetic modification, as well as excluding UiO-66 analogues such as UiO-67. The final data set (included in the Supporting Information) is intended to be a representative, but not a comprehensive summary of the current literature and comprises of 293 samples across 37 papers, ,,, ,,, representing a publication period from 2011 to 2022. The distribution of the data set across input and output variables is also presented in the Supporting Information.…”
Section: Data Collection and Characterizationmentioning
confidence: 99%
“…The aim of this review is to draw connections between synthetic parameters and the final defective structures reported in the literature to aid the experimental design of UiO-66 MOFs with specific defect properties; it is expected that other MOFs with similarly strong coordination bonds will have similar dependence on synthetic parameters. To assist with this goal, we conducted a literature meta-analysis with 293 samples across 37 papers ,,, ,,, looking for reliable trends between reaction parameters and structural outcomes, such as defect concentration. We fit a LASSO linear regression model relating the synthetic parameters studied (time, temperature, and reagent concentrations) to quantitative defectivity and other output variables.…”
Section: Introductionmentioning
confidence: 99%
“…Mguni et al reported that the modulated synthesis of Ni-BDC using formic acid increased the the overall adsorptive capacity by two folds [22]. The UIO-66 is regarded as a promising adsorbent due to its short synthesis time, low synthesis temperature, and massive preparation [23]. Moreover, MOFs-based materials as heterogeneous catalysts are also widely reported for the oxidative desulfurization.…”
Section: Introductionmentioning
confidence: 99%